2018
DOI: 10.1080/23743603.2018.1559647
|View full text |Cite
|
Sign up to set email alerts
|

The influence of gender stereotype threat on mathematics test scores of Dutch high school students: a registered report

Abstract: The effects of gender stereotype threat on mathematical test performance in the classroom have been extensively studied in several cultural contexts. Theory predicts that stereotype threat lowers girls' performance on mathematics tests, while leaving boys' math performance unaffected. We conducted a large-scale stereotype threat experiment in Dutch high schools (N = 2064) to study the generalizability of the effect. In this registered report, we set out to replicate the overall effect among female high school … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 93 publications
2
78
0
4
Order By: Relevance
“…Recently, researchers have raised questions around stereotype threat. Some have questioned whether stereotype threats lead to practically meaningful effect sizes (Shewach et al, 2019); others have been unable to replicate stereotype threat effects for women and girls in math (Ganley et al, 2013;Pennington et al, 2018;Flore et al, 2019), and still others are working on a meta-analysis examining whether the magnitude of stereotype threat effects is decreasing over time (Lewis and Michalak, 2019). Results of stereotype threat research on men in language in particular have been inconsistent, with significant findings reported for both impaired and improved performance after threat (Hirnstein et al, 2012;Pansu et al, 2016), as well as null results (Eckert and Imhof, 2013) and our present results showing evidence of no effect.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, researchers have raised questions around stereotype threat. Some have questioned whether stereotype threats lead to practically meaningful effect sizes (Shewach et al, 2019); others have been unable to replicate stereotype threat effects for women and girls in math (Ganley et al, 2013;Pennington et al, 2018;Flore et al, 2019), and still others are working on a meta-analysis examining whether the magnitude of stereotype threat effects is decreasing over time (Lewis and Michalak, 2019). Results of stereotype threat research on men in language in particular have been inconsistent, with significant findings reported for both impaired and improved performance after threat (Hirnstein et al, 2012;Pansu et al, 2016), as well as null results (Eckert and Imhof, 2013) and our present results showing evidence of no effect.…”
Section: Resultsmentioning
confidence: 99%
“…Some have questioned whether stereotype threats lead to practically meaningful effect sizes (Shewach et al, 2019), others have been unable to replicate stereotype threat effects for women and girls in math (Flore, Mulder, & Wicherts, 2019;Ganley et al, 2013;Pennington, Litchfield, McLatchie, & Heim, 2018), and still others are working on a meta-analysis examining whether the magnitude of stereotype threat effects is decreasing over time (Lewis & Michalak, 2019).…”
Section: Conclusion Stereotype Threat On Men In Language 31mentioning
confidence: 99%
“…As for stereotype threat, a recent slew of studies has failed to find evidence that situations likely to induce threat do in fact hamper females' performance in math or other cognitive domains. The studies in question include several meta-analyses (Flore & Wicherts, 2015;Stoet & Geary, 2012), a number of large, pre-registered replications (Finnigan & Corker, 2016;Flore et al, 2019), and an analysis of 5.5 million chess games played in international tournaments, which found that women's performance was better, rather than worse, under conditions of stereotype threat (Stafford, 2018). Meanwhile, on the other side of the ledger, a recent study failed to replicate the finding that stereotype threat impairs men's performance on tests of language ability (Chaffee et al, 2019).…”
Section: The Nature and Nurture Of Sex Differences In Cognitive Aptitmentioning
confidence: 99%